Characterizations of ZnO Nanoparticles Green Synthesized using Flaxseeds Extract for Biomedical Applications - Hasseb Elsayed, Yarou Mohssen; Mohd Yusoff, Mohd Zaki; Ahmad Kamil, Suraya; Md Idris, Muhd Hanis; Syed Mohamad, Sharifah Aminah; Yahya, Muhammad Syarifuddin; Abdul Halim Yap, Muhammad Firdaus Asyraf (Trends in Sciences, 2024)
ZnO-NPs were synthesized chemically and using the green synthesis technique by flaxseeds (Linum usitatissimum L.), which uses water to extract flaxseeds in a biologically convenient, secure and affordable manner, under different conditions of shape of flaxseed, grinded and full seeds, different concentrations of the precursor, zinc nitrate hexahydrate, (7.43, 14.87 and 22.31 g) each per 50 mL of distilled water to obtain (0.5, 1 and 1.5 mol/L) concentrations and different pH 8, 10, 12 and 13 and studying its characterizations using X-Ray diffraction (XRD) and field emission scanning electron microscopy (FESEM) to obtain the best ZnO-NPs size and morphological properties for biomedical uses. HIGHLIGHTS Green synthesized ZnO-NPs using flaxseed extract Whole seed flaxseed extract synthesizes ZnO-NPs with smaller size and spherical shape Higher zinc nitrate concentration increases ZnO-NPs size under pH 8 - 10 GRAPHICAL ABSTRACT